Implementation of the ASEAN Convention Against Trafficking in Persons, Particularly Women and Children (ACTIP) - Manafe, Maria Semy Nehemiya (Sekolah Tinggi Ilmu Kepolisian, 2026)
Human trafficking or trafficking in persons is a transnational crime that endangers global and regional security. Countries in the Southeast Asia region serve as origin, transit, and destination for trafficking in persons syndicates. In a unified effort to address this issue, ASEAN adopted the ASEAN Convention Against Trafficking in Persons, Especially Women and Children (ACTIP) in 2015, serving as a legally binding mechanism for regional cooperation to tackle trafficking in persons. Since its adoption, ACTIP has not been effectively implemented by ASEAN, as it has not reduced the number of TIP cases in the region. The primary mechanism, the ASEAN Senior Officials Meeting on Transnational Crime (SOMTC), solely functions in monitoring, facilitating coordination, evaluating, and compiling periodic reports on the implementation of the convention, lacking the authority to enforce compliance with ACTIP. In addition to the unique principles of the “ASEAN Way”, the challenges encountered by ASEAN in addressing trafficking in persons are notably intricate. To uncover the intricating issues, the author utilizes the Regional Security Complex Theory (RSCT) by Barry Buzan and Ole Waever to clarify the variables that hinder the effective implementation of ACTIP in ASEAN. The complexity of addressing trafficking in persons will be analysed at national, international, regional, and global levels using four RSCT variables: boundary, anarchic structures, power distribution, and social construction within the ASEAN organization. This study employs qualitative methodologies utilizing primary and secondary data sources, including scholarly literature, publications, and official reports from ASEAN bodies, government agencies, and international organizations. Given the identified issues, ASEAN must execute internal changes by strengthening the function of the SOMTC to create a cooperative framework at the technical level for the effective implementation of ACTIP.